Legal Protection for Consumers in E-commerce Expeditions: Perlindungan Hukum bagi Konsumen dalam Ekspedisi E-commerce - Sugito, Gea Ossita; HS, Salim; Wagian, Diangsa (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the legal protection afforded to consumers in the context of e-commerce, focusing on the liabilities of expedition services in cases of delayed or damaged goods. The primary objective is to explore the forms of legal protection provided to consumers for losses due to delays or damages in goods transported by expedition services, and to understand the legal responsibilities of these services in such scenarios. Utilizing a normative research method, the study examines relevant consumer protection laws and regulations governing shipment agreements. The findings reveal that consumers are entitled to various forms of legal protection, including the right to compensation in the form of refunds, replacement of goods, or payments based on the value of loss; entitlement to indemnities for healthcare costs or beneficiary allowances in cases of life-threatening harm; and the right to compensation from expedition services for material and immaterial losses beyond mere refunds. Additionally, the study underscores the government and consumer protection agencies' duty to educate and guide businesses, including expedition services. The legal responsibility of expedition services extends to compensating consumers for delayed shipments or lost goods, through either refunds or replacements. Moreover, the services are obligated to provide compensation or replacements for undelivered or damaged goods. Consumer claims for compensation can be resolved through direct negotiation with the expedition service, legal action, or alternative dispute resolution mechanisms like BPSK. The study concludes that while consumers are legally protected to obtain compensation from expedition services, the enforcement of these services' responsibilities needs to be strengthened for more optimal fulfillment of consumer rights.Highlights: Legal Protections: Consumers have the right to compensation, including refunds, replacements, or payment for losses, and indemnities for life-threatening damages. Expedition Services' Obligations: These services must compensate for delays, lost, or damaged goods, with options for direct negotiation, legal action, or alternative dispute resolution. Enforcement Needs: Despite existing protections, there is a necessity to strengthen the enforcement of expedition services' responsibilities to better fulfill consumer rights. Keywords: Consumer Protection, E-commerce, Legal Responsibilities, Expedition Services, Compensation Claims